Is slowness a better discriminator of disability than frailty in older adults?. Issue 6 (29th September 2021) - de Oliveira, Dayane Capra; de Oliveira Máximo, Roberta; Ramírez, Paula Camila; de Souza, Aline Fernanda; Luiz, Mariane Marques; Delinocente, Maicon Luis Bicigo; Chagas, Marcos Hortes Nisihara; Steptoe, Andrew; de Oliveira, Cesar; da Silva Alexandre, Tiago
Abstract: Background: The trajectory of incident disability that occurs simultaneously with changes in frailty status, as well as how much each frailty component contributes to this process in the different sexes, are unknown. The objective of this study is to analyse the trajectory of the incidence of disability on basic and instrumental activities of daily living (BADL and IADL) as a function of the frailty changes and their components by sex over time. Methods: Longitudinal analyses of 1522 and 1548 of the English Longitudinal Study of Ageing study participants without BADL and IADL disability, respectively, and without frailty at baseline. BADL and IADL were assessed using the Katz and Lawton Scales and frailty by phenotype at 4, 8, and 12 years of follow‐up. Generalized mixed linear models were calculated for the incidence of BADL and IADL disability, as an outcome, using changes in the state of frailty and its components, as the exposure, by sex in models fully adjusted for sociodemographic, behavioural, biochemical, and clinical characteristics. Results: The mean age, at baseline, of the 1522 eligible individuals free of BADL and free of frailty was 68.1 ± 6.2 years (52.1% women) and of the 1548 individuals free IADL and free frailty was 68.1 ± 6.1 years (50.6% women). Women who became pre‐frail had a higher risk of incidence of disability for BADL and IADL when compared with those who remained non‐frail ( P < 0.05). Men and women who became frail had a higher risk of incidence of disability regarding BADL and IADL when compared with those who remained non‐frail ( P < 0.05). Slowness was the only component capable of discriminating the incidence of disability regarding BADL and IADL when compared with those who remained without slowness ( P < 0.05). Weakness and low physical activity level in men and exhaustion in women also discriminated the incidence of disability ( P < 0.05). Conclusions: Slowness is the main warning sign of functional decline in older adults. As its evaluation is easy, fast, and accessible, screening for this frailty component should be prioritized in different clinical contexts so that rehabilitation strategies can be developed to avoid the onset of disability.